Metal-free coating comprising hydrogen-free tetrahedral amorphous carbon
By depositing multiple amorphous carbon films on the coated substrate and designing interface layers and transition layers, the problems of short service life and insufficient toughness in cutting or forming applications in the prior art are solved, and a coating structure with high toughness and wear resistance is achieved, which significantly improves the service life and performance of the tool.
Patent Information
- Application Number
- CN202380052127.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-06
- Filing Date
- 2023-07-06
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, amorphous carbon coatings have a short service life and are not tough enough to meet the high performance needs of tools in these applications.
By depositing a multi-layer amorphous carbon film on the coated substrate, the ratio of the percentage of the sp3 bonds of the bottom and top layers to the percentage of the C-C bonds gradually increases along the thickness direction, an optimized amorphous carbon film structure is formed. In addition, the design of the interface layer and the transition layer further improves the adhesion of the amorphous carbon film to the substrate.
High toughness and wear resistance of amorphous carbon coatings are achieved, significantly improving tool life and improving performance in cutting and forming applications.
Smart Images

Figure CN119563043A_ABST
Abstract
Description
[0001] The present invention relates to coated substrates, especially coated tools, and methods for making the same, having a metal-free coating comprising a hydrogen-free tetrahedral amorphous carbon film and having enhanced toughness. Prior art
[0002] Ohtan i et al. proposed in EP 1266979 B1 to manufacture amorphous carbon coated tools by specifying the composition of the substrate and the thickness of the amorphous carbon film. The method for manufacturing amorphous carbon coated tools proposed in EP 1266979 B1 includes the following steps: supporting a WC-based cemented carbide substrate in a vacuum container, applying a zero or negative DC bias to the substrate, and evaporating graphite as a source material to form an amorphous carbon film. The maximum thickness of the amorphous carbon film at the cutting edge is controlled to be 0.05 μm to 0.8 μm. It is recommended to use graphite as a material source for forming an amorphous carbon film by physical vapor deposition in a hydrogen-free atmosphere, so that the hydrogen content in the amorphous carbon film does not exceed 5 atomic%. In addition, it is particularly recommended to use a cathode arc ion plating method and a temperature between 50°C and 350°C.
[0003] In addition, Ohtan i et al. suggested using appropriate measures to prevent particles from scattering from graphite materials to improve the surface roughness of amorphous carbon films, such as by growing the film at low energy or by using a filter with the aid of a magnetic field. The suggested roughness Ra is between 0.002 μm and 0.05 μm. The suggested Knoop hardness is between 20 GPa and 50 GPa. Amorphous carbon films are transparent in the visible light range and show interference colors, where the color of the coated film can be a rainbow color showing multiple shades, rather than a single color. The coating tool has an intermediate layer arranged between the substrate and the amorphous carbon film to enhance the adhesion of the amorphous carbon film, wherein the intermediate layer can be made of at least one element selected from the group consisting of elements of Groups IVa, Va, VI a and III b and Group IVb (excluding carbon) of the periodic table, or a carbide of at least one element selected from the group consisting of these elements. In particular, it is recommended that the intermediate layer contain at least one element selected from the group consisting of elements Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W and Si, or a carbide of at least one element selected from the group consisting of these elements, and the thickness of the intermediate layer is between 0.5nm and 10nm.
[0004] Becker et al. proposed a method in WO 2021 / 019084 A1 for manufacturing a hydrogen-free amorphous carbon coating having a lower hardness close to the substrate and the outer surface of the coating and a higher hardness anywhere between these two areas. In order to obtain these desired coating transitions, Becker et al. proposed to deposit the hydrogen-free amorphous carbon coating by controlling the bias voltage and substrate temperature, combined with cathodic arc evaporation technology, and applying a low target current in the range of 25A to 35A. In addition, Becker et al. proposed depositing a metal layer as an adhesion layer to improve the adhesion between the substrate and the hydrogen-free amorphous carbon coating. Such a coating solution is very suitable for parts used in automotive applications, but not for tools used in cutting or forming applications.
[0005] Purpose of the Invention
[0006] The main object of the present invention is to provide a coated substrate, especially a coated tool, which exhibits tribological properties similar to those of hydrogen-free tetragonal amorphous carbon coatings, but preferably shows higher toughness than the prior art, especially with enhanced performance and longer service life, especially suitable for tools used in cutting or forming applications (i.e. in the case of coated tools, thus having enhanced tool performance and longer service life), without being affected by the hardness of the substrate. Summary of the invention
[0007] The present invention provides a coating solution, in particular a coated substrate as a first aspect and a method for producing the coated substrate according to the invention as a second aspect.
[0008] According to a main embodiment of the coated substrate of the present invention, a coated substrate as claimed in claim 1 is provided, which is preferably a coated tool used in a manufacturing process (such as a machining process or a forming process), comprising a coated surface, which is formed by a substrate surface made of a first material and a coating system applied to the substrate surface, wherein the coating system is preferably an arc PVD deposition coating system (PVD=physical vapor deposition), and the coating system comprises an amorphous carbon film, wherein the amorphous carbon film is a hydrogen-free tetrahedral amorphous carbon film, wherein the sp 3 The percentage of CC bonds exceeds that of sp 2 The percentage of keys.
[0009] According to the present invention, the amorphous carbon film 100 is preferably designed to have a variable sp 3 The percentage of CC bonds is similar to sp 2 The ratio of the bond percentages is as follows, wherein the ratio increases from the bottom side toward the top side of the amorphous carbon film 100, for example, continuously and / or stepwise, wherein the bottom side is the area of the amorphous carbon film 100 closest to the substrate and the top side is the area of the amorphous carbon film 100 farthest from the substrate.
[0010] According to a preferred embodiment, the amorphous carbon film 100 is formed as a multilayer film including at least two hydrogen-free tetrahedral crystalline carbon layers, wherein the at least two layers are:
[0011] - a bottom layer 120, which includes the region of the amorphous carbon film 100 closest to the substrate, and
[0012] - a top layer 150, which includes the region of the amorphous carbon film 100 that is farthest from the substrate, wherein the sp 3 The percentage of CC bonds is similar to sp 2 The key percentage ratio is greater.
[0013] In a most preferred embodiment, the top layer 150 is the outermost layer of the amorphous carbon film 100. This allows, inter alia, a tool coated in this way to have a high tool performance, especially when the coated tool is used in cutting and forming applications.
[0014] In order to improve the adhesion of the amorphous carbon film 100 to the substrate, the amorphous carbon film 100 is preferably deposited on the surface of the substrate in such a way that an interface layer 10 is formed between the first material 1 on the surface of the substrate and the amorphous carbon film 100, wherein the interface layer 10 is composed of a carbon-injected material, and the carbon-injected material is composed of a first material and carbon injected therein, wherein the thickness of the interface layer 10 is at least 3 nm.
[0015] In order to further improve the adhesion of the amorphous carbon film 100 to the substrate, a transition layer 30 is deposited between the interface layer 10 and the amorphous carbon film 100 , wherein the transition layer 30 is a carbon layer that improves the interface transition between the interface layer 10 and the amorphous carbon film 100 .
[0016] Preferably, the transition layer 30 is a hydrogen-free tetrahedral amorphous carbon layer.
[0017] According to a very preferred embodiment of the present invention, the amorphous carbon film 100 has a low residual compressive stress, which corresponds to an absolute value not greater than 5.5 GPa, preferably in the range of 2.8 GPa to 5.5 GPa, and more preferably in the range of 3 GPa to 5 GPa (the value is determined in particular by using known Micro-Epsilon coating internal stress measurements).
[0018] In addition, the amorphous carbon film 100 preferably includes at least one portion, such as a layer, which exhibits a ratio of an average Young's modulus to an average hardness (both properties are measured in GPa using standard nanoimprint techniques) in the range of 7 to 13, preferably in the range of 8 to 12.
[0019] The bottom layer 120 preferably has a hardness in the range of 30 GPa to 50 GPa, preferably in the range of 30 GPa to 45 GPa, and the top layer 150 preferably has a hardness in the range of greater than 50 GPa to 80 GPa, more preferably in the range of 55 GPa to 80 GPa, especially from 55 GPa to 75 GPa.
[0020] The bottom layer 120 preferably has a Young's modulus in the range of 250 GPa to 350 GPa, and the top layer 150 preferably has a Young's modulus in the range of 500 GPa to 800 GPa.
[0021] The transition layer 30 preferably has a hardness in the range of greater than 50 GPa to 80 GPa, preferably in the range of 55 GPa to 80 GPa or in the range of 55 GPa to 75 GPa, and / or has a Young's modulus in the range of 500 GPa to 800 GPa.
[0022] Depending on the application, the amorphous carbon film (100) can be manufactured to have a specific color or combination of colors.
[0023] Therefore, in some cases, the amorphous carbon film 100 manufactured displays multiple tones instead of a single color, such as a rainbow appearance to the human eye under visible light; and in other cases, the amorphous carbon film 100 manufactured displays a single color, such as a black or gray appearance to the human eye under visible light.
[0024] According to another preferred embodiment of the present invention, the amorphous carbon film 100 includes at least one layer having a maximum thickness along the entire amorphous carbon film 100, sp 3 The percentage of CC bonds is similar to sp 2 The ratio of the percentage of bonds is preferably such that, for example, the highest thickness of the amorphous carbon film 100 and the highest sp are obtained in order to obtain the maximum cutting performance or forming performance. 3 The percentage of CC bonds is similar to sp 2 The at least one layer having a key percentage ratio is the top layer 150 .
[0025] To achieve the desired performance, it is preferred that:
[0026] o the interface layer 10 is in the range of 3 nm to 200 nm, more preferably in the range of 3 nm to 100 nm, still more preferably in the range of 3 nm to 50 nm, and / or
[0027] o The transition layer 30 has a thickness in the range of 10 nm to 200 nm, preferably in the range of 15 nm to 100 nm, and more preferably in the range of 15 nm to 70 nm.
[0028] Also preferred are:
[0029] o the thickness of the bottom layer 120 is in the range of 30 nm to 2000 nm, preferably in the range of 30 nm to 500 nm, and more preferably in the range of 50 nm to 300 nm, and / or
[0030] o The thickness of the top layer 150 is in the range of 50 nm to 1000 nm, preferably in the range of 50 nm to 500 nm, and even more preferably in the range of 70 nm to 350 nm.
[0031] In order to obtain higher wear resistance and toughness, it is preferred that:
[0032] o The average hardness of the amorphous carbon film 100 is in the range of 50 GPa to 80 GPa, preferably in the range of 50 GPa to 70 GPa, and / or
[0033] o The average Young's modulus of the amorphous carbon film 100 is in the range of 500 GPa to 800 GPa, more preferably in the range of 600 GPa to 750 GPa.
[0034] The amorphous carbon film according to the present invention preferably shows a friction coefficient in the range of 0.05 to 0.15 as measured by a ball-on-disk test.
[0035] The present invention not only relates to the individual forms of the above-mentioned embodiments, but also encompasses all possible combinations thereof.
[0036] A preferred method for producing a coated substrate according to any of the preceding embodiments and combinations thereof comprises the following method steps:
[0037] providing a substrate having a surface to be coated made of a first material 1,
[0038] The amorphous carbon film 100 is deposited by using a PVD process, wherein the PVD process involves cathodic arc evaporation of one or more graphite targets and applying a negative bias voltage to the substrate to be coated, wherein the absolute value of the bias voltage varies during the deposition of the amorphous carbon film 100 as follows, i.e., sp 3 The percentage of CC bonds is similar to sp 2 The ratio of the bond percentages varies along its thickness such that it has its lowest value at the beginning of the deposition of the amorphous carbon film 100 and has its lowest value at the end of the deposition of the amorphous carbon film 100, wherein the absolute value of the bias voltage applied at the beginning of the amorphous carbon film 100 deposition process is lower than the absolute value of the bias voltage at the end of the amorphous carbon film 100 deposition process.
[0039] The absolute bias voltage applied during the deposition of the amorphous carbon film 100 is preferably selected to vary in the range of 0V to 200V, more preferably 10V to 180V, and even more preferably 10V to 150V.
[0040] In order to deposit different layers within the amorphous carbon film 100, the inventors suggest to keep the bias voltage value as constant as possible for depositing different layers of the same layer with the same specified properties.
[0041] The absolute arc current applied to the one or more graphite targets during deposition of the amorphous carbon film 100 is preferably selected to be a value in the range of 50A to 110A.
[0042] During the deposition of the amorphous carbon film 100, preferably at least a bottom layer 120 is deposited first, followed by a top layer 150, wherein the absolute value of the bias voltage used during the deposition of the bottom layer 120 is lower than the absolute value of the bias voltage used during the deposition of the top layer 150.
[0043] More preferred are:
[0044] To deposit the bottom layer (120), a negative bias voltage in the absolute range of 0V to 50V and an arc current in the range of 50A to 110A is used, and / or
[0045] • For depositing the top layer (150), a negative bias voltage in the absolute value range of 50V to 200V, preferably 50V to 180V, more preferably 50V to 150V and an arc current in the range of 50A to 110A is used.
[0046] In order to form the interface layer 10, the method preferably comprises the following method steps:
[0047] Prior to the deposition of the amorphous carbon film 100, the interface layer 10 is manufactured in the following manner, i.e., the first material 1 is bombarded with carbon ions from at least one carbon target (preferably at least one carbon target in the form of a graphite target), in such a way that a carbon implanted material constituting the interface layer 10 is formed, wherein preferably, a PVD process is used to generate the carbon ions, which involves an arc evaporation technique, preferably applying an arc current in the range of 30 A to 50 A, and preferably using a bias voltage in the range of 400 V and 1000 V.
[0048] In order to form the transition layer 30, the method preferably comprises the following method steps:
[0049] After the deposition of the interface layer (10) and before the deposition of the amorphous carbon film (100), the transition layer (30) is manufactured by using a PVD process, wherein the PVD process involves cathodic arc evaporation of one or more graphite targets and applying a negative bias voltage to the substrate to be coated, wherein the absolute value of the bias voltage changes during the deposition of the transition layer (30), wherein preferably, the absolute value of the bias voltage applied at the beginning of the deposition process of the transition layer (30) is the same as the absolute value of the bias voltage used when forming the interface layer (10), and it is reduced to an absolute value in the range of 150V to 200V.
[0050] Preferably, the amorphous carbon film (100) is deposited by maintaining the process temperature in the range of 70°C to 180°C, preferably in the range of 80°C to 170°C, and even more preferably in the range of 100°C to 140°C.
[0051] The amorphous carbon film is deposited on the substrate surface such that an interface layer is formed between the first material on the substrate surface and the amorphous carbon film, wherein the interface layer is composed of carbon implanted into the first material, and wherein the thickness of the interface layer is at least 3 nm.
[0052] Therefore, according to the present invention:
[0053] o It is conceivable to design the amorphous carbon film to have a variable, sp 3 The percentage of CC bonds is similar to sp 2 The ratio of the bond percentages preferably increases from the bottom side toward the top side of the amorphous carbon film.
[0054] o It is contemplated that the amorphous carbon film includes at least one layer having a maximum thickness along the amorphous carbon film, sp 3 The percentage of CC bonds is similar to sp 2 Key percentage ratio.
[0055] o It is conceivable that the highest thickness along the amorphous carbon film, sp 3 The percentage of CC bonds is similar to sp 2 The at least one layer having a bond percentage ratio of 0.1 to 0.2 is preferably deposited as the outermost layer 150 (also referred to as the top layer 150 ) of the amorphous carbon film 100 .
[0056] o It is contemplated that the amorphous carbon film 100 may be preferably deposited in a multilayer form (i.e., including at least two layers), wherein the at least two layers are designed so as to achieve a combination of excellent toughness and low residual compressive stress. To achieve this technical effect, the at least two layers are a bottom layer 120 and a top layer 150, wherein the thickness along the top layer 150 is greater than the thickness along the bottom layer 120, sp 3 The percentage of CC bonds is similar to sp 2 The ratio of the bond percentage is greater. It is conceivable that the amorphous carbon film 100 may include at least one portion, such as a layer, which is transparent in the visible light range and exhibits interference colors, wherein the color of the amorphous carbon film may be a rainbow color showing multiple tones instead of a single color, or the amorphous carbon film 100 may include at least one portion, such as a layer, which exhibits a prescribed color, such as a black appearance.
[0057] o It is contemplated that the amorphous carbon film preferably includes at least one portion, such as a layer, which exhibits a ratio of an average Young's modulus to an average hardness (both properties are expressed in GPa as measured using standard nanoimprint techniques) in the range of 7 to 13, preferably in the range of 8 to 12.
[0058] o It is conceivable that the interface layer thickness is in the range of 3 nm to 200 nm, preferably in the range of 3 nm to 100 nm.
[0059] o It is envisaged that the interface layer thickness may even more preferably be in the range of 3 nm to 50 nm.
[0060] o It is also conceivable that the interface layer does not contain any liquid droplets.
[0061] o It is conceivable that the average hardness of the amorphous carbon film is in the range of 50 GPa to 80 GPa, preferably in the range of 50 GPa to 70 GPa.
[0062] o The average Young's modulus of the amorphous carbon film may be in the range of 500 GPa to 800 GPa, preferably in the range of 600 GPa to 750 GPa.
[0063] o It is also conceivable that the amorphous carbon film is formed as a multilayer film, which includes at least two hydrogen-free tetrahedral amorphous carbon layers, preferably more than two hydrogen-free tetrahedral amorphous carbon layers.
[0064] o Amorphous carbon films can exhibit a coefficient of friction in the range of 0.05 to 0.15 as measured by a ball-on-disk test.
[0065] o In another aspect of the invention it is conceivable to provide a method for producing a coated substrate according to the invention. The material forming the interface layer is produced by bombarding a first material with carbon ions, the first material forming the substrate surface of the tool to be coated, and
[0066] No metal layer is contained, and the amorphous carbon film is directly deposited on the second material by using a PVD process, wherein the PVD process involves cathodic arc evaporation of a graphite target and applying a negative bias voltage to the substrate to be coated, wherein the absolute value of the bias voltage changes during the amorphous carbon film deposition as follows, i.e., the absolute value of the bias voltage at the beginning of the amorphous carbon film 100 deposition process is higher than the absolute value of the bias voltage at the end of the amorphous carbon film deposition process.
[0067] o It is conceivable that the absolute value of the bias voltage changes stepwise.
[0068] o It is also conceivable that the absolute value of the bias voltage varies within the range of 0V to 600V, preferably within the range of 10V to 500V.
[0069] o It is also conceivable that the absolute value of the arc current varies in the range of 35A to 80A, preferably in the range of 40A to 70A.
[0070] o Amorphous carbon films may be deposited by maintaining the process temperature in the range of 80°C to 170°C, preferably in the range of 100°C to 140°C.
[0071] o It is conceivable that during the amorphous carbon film deposition process, coating parameters are adjusted to reduce droplets within the amorphous carbon film.
[0072] In order to explain the present invention more specifically, some examples will be explained below, and Figures 1 to 10 The examples and illustrations should not be construed as limiting the present invention.
[0073] An example of deposition of a coating according to the invention is as follows:
[0074] The substrate is coated with a coating composed of hydrogen-free tetrahedral amorphous carbon.
[0075] Substrates of different types and materials are cleaned and fed into the vacuum coating chamber of the Oerlikon DOM INO SC and DOM INO L coating equipment.
[0076] In particular, the following substrates were coated, observed and / or tested:
[0077] 1) Quality reference samples made of the following materials:
[0078] a. Steel type: 90MnCrV8 and 1.2842, with hardness higher than 62HRC, arithmetic average roughness Ra≤0.05μm, size
[0079] b. Cemented carbide SPGN 120308, containing 6 wt% cobalt, with dimensions of 12x12mm and a thickness of 3.18mm, and
[0080] 2) Cutting tools and forming tools of the following types:
[0081] a. Drills, milling cutters, reamers, taps, punches, cutting knives, dies, dies, finishing tools,
[0082] b. Flanging tools, made of carbide, high-speed steel, D2 steel, H13 steel and CuBe tools respectively.
[0083] A vacuum was generated in the vacuum coating chamber until a vacuum condition corresponding to a pressure of 0.08 Pa was reached.
[0084] Next, an argon flow in the range of 50 sccm to 300 sccm is used as a process gas, preferably, the argon flow is maintained at a value in the range of 150 sccm to 250 sccm. The argon flow is introduced into the vacuum coating chamber, and the flow rate varies according to the process pressure adjustment during the process, that is, the process is performed under pressure control.
[0085] During the deposition of the amorphous carbon coating, the entire process pressure is maintained at a pressure value in the range of 0.05 Pa to 1.5 Pa.
[0086] Formation of carbon-rich interface (interface layer 10)
[0087] Prior to coating deposition, the substrate surface to be coated is bombarded with carbon ions to form carbon implants at the interface between the substrate surface to be coated and the coating deposited on the substrate, thereby enhancing the adhesion of the coating to the substrate surface by adding an adhesion layer between the substrate surface and the coating without compromising tool performance.
[0088] During the carbon ion bombardment, the carbon ions are able to penetrate the surface of the substrate to be coated to a depth ranging from 3 nm to 30 nm, thereby forming a carbon-rich interface layer, which can be observed from the following SEM images, which clearly show that carbon is embedded in the substrate material, such as carbon embedded in the steel matrix.
[0089] After forming the interface layer, the process parameters are adjusted to trigger the formation of the amorphous carbon film. To form the amorphous carbon film, a graphite target is used as a coating source material, wherein carbon from the graphite target is evaporated into a vacuum coating chamber using a cathodic arc ion plating method in an atmosphere containing only argon as the only process gas.
[0090] The inventors observed that, impressively, the absence of a metallic intermediate layer, such as a chromium intermediate layer that is often deposited to enhance adhesion between a substrate and a coating, resulted in a significant enhancement of adhesion between the coating and the substrate. The inventors believe that this significant improvement may be due to the fact that no droplets are formed at the interface between the surface of the substrate to be coated and the coating, since no metallic layer is deposited in between, and droplets are usually also generated during the deposition of the metallic intermediate layer, which is deposited together with the metallic intermediate layer, and therefore, the absence of droplets results in enhanced adhesion.
[0091] A coating consisting of hydrogen-free tetrahedral amorphous carbon is then deposited using a cathodic arc evaporation technique.
[0092] The method for coating the substrate in the above-described examples of the present invention is described in more detail below:
[0093] After the substrate has been cleaned, placed in the vacuum coating chamber and evacuated, it is subjected to the following further process steps:
[0094] Preheat
[0095] The substrate was heated to about 100° C. in the same vacuum coating chamber used for carbon implantation. The preheating step employed radiant heaters located within the vacuum coating chamber.
[0096] Etching
[0097] The surface of the substrate to be coated is etched using argon ions. Etching is carried out by the so-called "Advanced Energy Glow Discharge" (AEGD) technology. In the vacuum coating chamber, the titanium target is placed behind a valve and activated by an arc with a target current of 80A. The titanium ions produced are captured by the valve. By applying a positive potential to the rods in the chamber, the electrons produced by this process are directed to the surface of the substrate to be coated for etching. During this stage, an argon gas flow is sent into the vacuum coating chamber and pressure control is performed at a pressure value of about 1Pa. By applying a negative bias voltage with an absolute value in the range of 50V to 200V to the substrate, the ionized argon (Ar+) thus produced is directed to the surface of the substrate to be coated. The surface of the substrate to be coated is then etched by ion bombardment in this way.
[0098] The carbon ion bombardment step for forming the carbon-rich interface (interface layer 10) of the present invention is exemplified in more detail as follows.
[0099] Carbon is doped into a steel or cemented carbide substrate by using an argon gas flow in the range of 50 sccm to 300 sccm (e.g., about 250 sccm) at a process pressure in the range of 0.01 Pa to 0.02 Pa (e.g., about 0.015 Pa). Argon gas is injected directly in front of a carbon-containing target (e.g., a graphite target) through a gas shower. The carbon-containing target is ignited by a trigger wire and operated at a target current in the range of 40 A to 55 A (e.g., about 45 A). The generated carbon ions (C+) are then accelerated to the surface of the substrate to be coated by applying a negative bias voltage with an absolute value in the range of 500 V to 700 V (e.g., about 500 V), so that the carbon ions are micro-injected into the substrate below the surface of the substrate to be coated.
[0100] Deposition of the carbon transition layer (transition layer 30)
[0101] The absolute value of the negative bias voltage value is reduced, for example, from 500 V to 250 V or lower. Deposition of Hydrogen-Free Tetrahedral Amorphous Carbon Film (also referred to as ta-C Film or Amorphous Carbon Film 100)
[0102] The hydrogen-free tetrahedral amorphous carbon film (ta-C film) is produced at the same process pressure used in the previous process step, but the argon gas flow used is in the range of 50 sccm to 80 sccm, for example, between 60 sccm and 70 sccm. In this case, the carbon-containing target (such as a graphite target) is operated at a higher target current, for example, in the range of 60 A to 90 A. The absolute value of the negative bias voltage increases at a certain rate (for example, the increase is carried out in a ramp or stepwise manner, for example, two different layers, such as the bottom layer 120 and the top layer 150, are formed in two steps) during the entire coating process (here, it refers to the entire deposition process of the amorphous carbon film 100), from 10 V to 250 V or from 10 V to 100 V or lower.
[0103] The target current of the carbon-containing target was kept constant.
[0104] An advantage of applying a lower bias voltage at the beginning of the coating process is that it produces a ta-C layer (such as the bottom layer 120) with a lower hardness.
[0105] Next, further increasing the absolute value of the bias voltage allows deposition of a ta-C layer having a higher hardness (i.e., a harder ta-C layer, such as the top layer 150), whose hardness is measured by a known nanoimprint method (e.g., using a Fisherscope nanoimprint device), e.g., in the range of 50 GPa to 80 GPa.
[0106] By using a negative bias voltage of about -80 V and a substrate temperature close to 120 °C, the sp 3 key ratio, and can also reduce sp 2 This results in a very hard diamond-like top layer, which has a much higher hardness than the rest of the coating, about 60-80 GPa, i.e. in the range of 60 GPa to 80 GPa. This significantly harder top layer is believed to offer significant advantages in cutting applications as well as in forming applications.
[0107] In order to analyze the performance of the coatings of the present invention, various standard characterization tests or characterization techniques are used, such as:
[0108] - Scanning electron microscopy (SEM),
[0109] -Nano scratch test for comparing coating adhesion performance,
[0110] - Secondary ion mass spectrometry,
[0111] - Transmission Emission Microscopy (TEM),
[0112] - Micro-Epsili on measurement of internal stresses in coatings (calculated from known residual stresses (also called internal stresses) in thin material specimens, for which DIN Technical Report 30 {also known as DIN Professional Report 39} is used, see page 163). BRIEF DESCRIPTION OF THE DRAWINGS
[0113] Figure 1 The design of a coated substrate according to the prior art is schematically shown, which includes a substrate 1 , a metal adhesion layer 20 and an amorphous carbon film 100 .
[0114] Figure 2 The design of a coated substrate according to the present invention is schematically shown, which comprises a substrate 1 , an interface layer 10 and an amorphous carbon film 100 .
[0115] Figure 3 The design of a preferred embodiment of the coated substrate according to the present invention is schematically shown, wherein the amorphous carbon film 100 includes a top layer 150, the sp 3 The content of bonds is 120 greater than that of the bottom layer.
[0116] Figure 4: Figure 4a The design of another preferred embodiment of the coated substrate is schematically shown, in which the coating according to the present invention has a multilayer structure, in which an interface layer 10 and a transition layer 30 are deposited between the substrate surface 1 and the amorphous carbon film 100, and the amorphous carbon film 100 includes a bottom layer 120 and a top layer 150; Figure 4b SEM images are shown, which show that the Figure 4a A cross section of a coated substrate of a schematically shown multilayer structure.
[0117] FIG. 5 shows two SEM surface images showing that the surface of the coated substrate according to the prior art ( Figure 5a ) and the coated surface of the coated substrate according to the present invention ( Figure 5b ) between the surface quality differences.
[0118] Figure 6 A comparison between coating adhesion tests of coated substrates according to the prior art and coated substrates according to the present invention is shown. The coating adhesion was tested by a nano scratch test under the same conditions. The test was carried out with a 0.3N starting load and a scratch speed of 5mm / s.
[0119] Figure 7 and Figure 8 SIMS of the claimed coating on 100Cr6 steel and WC:Co substrates are shown. Trace amounts of chromium (less than 1 atomic %) impurities were detected due to the use of metallic chromium to treat the coating chamber. Figure 7 Specifically, the SIMS depth profile of the metal-free ta-C coating film of the present invention on a 100Cr6 steel substrate is shown. Figure 8 Specifically shown is the SIMS depth profile of the same inventive metal-free coating, but with a ta-C coating film deposited on a WC:Co substrate (cemented carbide).
[0120] Fig. 9 Shown is an SEM cross section of a metal-free coating deposited according to the present invention, including a taC coating.
[0121] Fig.10 The coating residual stresses of three different coatings of the present invention are shown, the coating of the present invention comprising an interface layer 10, a transition layer 30 and an amorphous carbon film 100 comprising a bottom layer 120 and a top layer 150, which are measured by using Micro-Epsilon coating internal stress measurement.
[0122] like Fig.10 As shown, residual stress values (in all these cases residual compressive stress values) are obtained from three different coatings of the present invention, but all three coatings have the following Figure 4a The multilayer structure shown in FIG. 1 and the total coating thickness is 600 nm. The residual compressive stresses of the three coating variants of the present invention are respectively -4.2 GPa, which are significantly lower than the comparative coatings of the prior art that do not have the structure of the present invention. For example, the prior art having Figure 1 The residual compressive stress of the coating with the structure shown and a total coating thickness of 400 nm is -6.128 GPa, which is significantly higher than the stress measurement results such as Fig.10 The variant of the invention is shown.
[0123] The invention is suitable for depositing very thin films, which allows coating of precision tools and parts for different applications, such as:
[0124] - cutting tools with sharp edges and / or complex geometries, as well as forming tools (such as dies) that require very high precision (e.g. no changes in geometry),
[0125] -Components or surfaces for semiconductor applications.
[0126] Furthermore, the present invention allows coating of a wide variety of possible substrate materials, such as aluminum (Al) and aluminum alloys, copper-beryllium (Cu-Be and copper-beryllium alloys), various steel grades, various cemented carbide types, and ceramics, among others.
Claims
1. A coated substrate, preferably a coating tool used in a manufacturing process, such as a machining process or a forming process, wherein the coated substrate has a coated surface, wherein the coated surface is formed by a substrate surface made of a first material (1) and a coating system applied to the substrate surface, wherein the coating system is preferably an arc PVD deposition coating system, wherein the coating system comprises an amorphous carbon film (100), wherein: The amorphous carbon film (100) is a hydrogen-free tetrahedral amorphous carbon film, wherein the sp 3 The percentage of CC bonds exceeds that of sp 2 Key percentage, Its characteristics are: ●The amorphous carbon film (100) is designed such that: its sp 3 The percentage of CC bonds and sp 2 The ratio of bond percentages is variable along its thickness, wherein the ratio increases from the bottom side toward the top side of the amorphous carbon film (100), for example, continuously and / or stepwise, wherein the bottom side is the area of the amorphous carbon film (100) closest to the substrate, and the top side is the area of the amorphous carbon film (100) farthest from the substrate.
2. The coated substrate according to claim 1, characterized in that: The amorphous carbon film (100) is formed as a multilayer film including at least two hydrogen-free tetrahedral amorphous carbon layers, wherein the at least two layers are: - a bottom layer (120) comprising a region of the amorphous carbon film (100) closest to the substrate, and - a top layer (150) comprising a region of the amorphous carbon film (100) that is furthest from the substrate, wherein the thickness of the top layer (150) is greater than the thickness of the bottom layer (120). 3 The percentage of CC bonds is related to sp 2 The "Key Percentage Ratio" is higher.
3. The coated substrate according to claim 2, characterized in that: The top layer (150) is the outermost layer of the amorphous carbon film (100).
4. The coated substrate according to at least one of the preceding claims 1 to 3, characterized in that The amorphous carbon film (100) is deposited on the surface of the substrate such that an interface layer (10) is formed between the first material (1) on the surface of the substrate and the amorphous carbon film (100), wherein the interface layer (10) is composed of a carbon-injected material, and the carbon-injected material is composed of the first material and carbon injected therein, and wherein the thickness of the interface layer (10) is at least 3 nm.
5. The coated substrate according to claim 4, characterized in that: A transition layer (30) is deposited between the interface layer (10) and the amorphous carbon film (100), wherein the transition layer (30) is a carbon layer that improves the interface transition between the interface layer (10) and the amorphous carbon film (100).
6. The coated substrate according to claim 5, characterized in that: The transition layer (30) is a hydrogen-free tetrahedral amorphous carbon layer.
7. The coated substrate according to at least one of the preceding claims 1 to 6, characterized in that The amorphous carbon film (100) has a low residual compressive stress, the absolute value of which is no greater than 5.5 GPa, preferably in the range of 2.8 GPa to 5.5 GPa, and more preferably in the range of 3 GPa to 5 GPa.
8. The coated substrate according to at least one of the preceding claims 1 to 7, characterized in that ●The amorphous carbon film (100) includes at least one portion, such as a layer, which exhibits a "ratio of average Young's modulus to average hardness" in the range of 7 to 13, preferably in the range of 8 to 12, both properties are measured in GPa using standard nanoimprint techniques.
9. The coated substrate according to at least one of the preceding claims 2 to 8, characterized in that The hardness of the bottom layer (120) is in the range of 30 GPa to 50 GPa, preferably in the range of 30 GPa to 45 GPa, and The hardness of the top layer (150) is in the range of greater than 50 GPa to 80 GPa, preferably in the range of 55 GPa to 80 GPa, or 55 GPa to 75 GPa.
10. The coated substrate according to at least one of the preceding claims 2 to 9, characterized in that The Young's modulus of the bottom layer (120) is in the range of 250 GPa to 350 GPa, and • The Young's modulus of the top layer (150) is in the range of 500 GPa to 800 GPa.
11. The coated substrate according to at least one of the preceding claims 5 to 10, characterized in that - the hardness of the transition layer (30) is in the range of greater than 50 GPa to 80 GPa, preferably in the range of 55 GPa to 80 GPa, or in the range of 55 GPa to 75 GPa, and / or - The Young's modulus of the transition layer is in the range of 500 GPa to 800 GPa.
12. The coated substrate according to at least one of the preceding claims 1 to 11, characterized in that The amorphous carbon film (100) exhibits multiple tones rather than a single color, for example, a rainbow appearance to the human eye under visible light.
13. The coated substrate according to at least one of the preceding claims 1 to 11, characterized in that The amorphous carbon film (100) exhibits a monochromatic color, for example, a black or gray appearance under visible light to the human eye.
14. The coated substrate according to at least one of the preceding claims 1 to 13, characterized in that The amorphous carbon film (100) comprises at least one layer, wherein the at least one layer has a maximum value of the "sp 3 The percentage of CC bonds is related to sp 2 Key Percentage Ratio".
15. The coated substrate according to claim 14, characterized in that · Having the highest "sp 3 The percentage of CC bonds is related to sp 2 The at least one layer having a "key percentage ratio" is the top layer (150).
16. The coated substrate according to at least one of the preceding claims 4 to 15, characterized in that ● the thickness of the interface layer (10) is in the range of 3nm to 200nm, preferably 3nm to 100nm, more preferably 3nm to 50nm, and / or The thickness of the transition layer (30) is in the range of 10 nm to 200 nm, preferably in the range of 15 nm to 100 nm, and more preferably in the range of 15 nm to 70 nm.
17. The coated substrate according to at least one of the preceding claims 4 to 16, characterized in that The thickness of the bottom layer (120) is in the range of 30 nm to 2000 nm, preferably in the range of 30 nm to 500 nm, and more preferably in the range of 50 nm to 300 nm, and / or • The thickness of the top layer (150) is in the range of 50 nm to 1000 nm, preferably in the range of 50 nm to 500 nm, even more preferably in the range of 70 nm to 350 nm.
18. The coated substrate according to at least one of the preceding claims 1 to 17, characterized in that ● the average hardness of the amorphous carbon film (100) is in the range of 50 GPa to 80 GPa, Preferably it is in the range of 50 GPa to 70 GPa.
19. The coated substrate according to at least one of the preceding claims 1 to 18, characterized in that The average Young's modulus of the amorphous carbon film (100) is in the range of 500 GPa to 800 GPa, preferably in the range of 600 GPa to 750 GPa.
20. A coated substrate according to any one of the preceding claims, characterised in that The amorphous carbon film exhibits a friction coefficient ranging from 0.05 to 0.15 as measured by a ball-on-disk test.
21. A method for producing a coated substrate according to any one of the preceding claims 1 to 20, characterized in that The method comprises the following steps: providing a substrate having a surface to be coated made of a first material (1), Depositing an amorphous carbon film (100) by a PVD process, wherein the PVD process involves cathodic arc evaporation of one or more graphite targets and applying a negative bias voltage to the substrate to be coated, wherein the absolute value of the bias voltage varies during the deposition of the amorphous carbon film (100) in the following manner, i.e., "sp 3 The percentage of CC bonds is related to sp 2 The ratio of the percentage of bonds varies along its thickness so that the absolute value of the bias voltage has its lowest value at the beginning of the deposition of the amorphous carbon film (100) and has its lowest value at the end of the deposition of the amorphous carbon film (100), wherein the absolute value of the bias voltage applied at the beginning of the deposition process of the amorphous carbon film (100) is lower than the absolute value of the bias voltage at the end of the deposition process of the amorphous carbon film (100).
22. The method according to claim 21, characterized in that: The absolute bias voltage applied during the deposition of the amorphous carbon film (100) varies within the range of 0V to 200V, preferably within the range of 10V to 180V, more preferably from 10V to 150V.
23. The method according to at least one of the preceding claims 21 to 22, characterized in that • During the deposition of the amorphous carbon film (100), an arc current in the range of 50A to 110A is applied to the one or more graphite targets.
24. The method according to at least one of the preceding claims 21 to 23, characterized in that During the deposition of the amorphous carbon film (100), at least the bottom layer (120) is deposited first and then the top layer (150) is deposited, wherein the absolute value of the bias voltage used during the deposition of the bottom layer (120) is lower than the absolute value of the bias voltage used during the deposition of the top layer (150), and preferably: ● for depositing the bottom layer (120), a negative bias voltage in the range of 0V to 50V absolute and an arc current in the range of 50A to 110A are used, and / or • To deposit the top layer (150), a negative bias voltage in the absolute range of 50V to 200V, preferably 50V to 180V, more preferably 50V to 150V and an arc current in the absolute range of 50A to 110A is used.
25. The method according to at least one of the preceding claims 21 to 24, characterized in that The method comprises the following steps: ● Prior to depositing the amorphous carbon film (100), an interface layer (10) is produced in the following manner, i.e., a carbon implanted material constituting the interface layer (10) is formed by bombarding the first material (1) with carbon ions originating from at least one carbon target, wherein the at least one carbon target is preferably a graphite target, wherein the carbon ions are preferably produced by using a PVD process involving arc evaporation technology, preferably applying an arc current in the range of 30A to 50A and preferably using a bias voltage in the range of 400V to 1000V.
26. The method according to claim 25, characterized in that: The method comprises the following steps: ●After the deposition of the interface layer (10) and before the deposition of the amorphous carbon film (100), a transition layer (30) is produced by using a PVD process, wherein the PVD process involves cathodic arc evaporation of one or more graphite targets and applying a negative bias voltage to the substrate to be coated, wherein the absolute value of the bias voltage changes during the deposition of the transition layer (30), wherein preferably, the absolute value of the bias voltage applied at the beginning of the transition layer (30) deposition process is the same as the absolute value of the bias voltage used when forming the interface layer (10) and is reduced to an absolute value in the range of 150V to 200V.
27. The method according to at least one of the preceding claims 21 to 25, characterized in that The amorphous carbon film (100) is deposited by maintaining the process temperature in the range of 70°C to 180°C, preferably 80°C to 170°C, and more preferably 100°C to 140°C.
Citation Information
Patent Citations
Amorphous carbon coated tool and fabrication method thereof
EP1266979B1
Graded hydrogen-free carbon-based hard material layer coated onto a substrate
WO2021019084A1